Neuropsychological correlates of hippocampal atrophy in memory testing in nondemented older adults - Vyhnalek, Martin; Nikolai, Tomas; Andel, Ross; Nedelska, Zuzana; Rubínová, Eva; Marková, Hana; Laczó, Jan; Bezdicek, Ondrej; Sheardova, Katerina; Hort, Jakub (Journal of Alzheimer's disease, 2014)
BACKGROUND AND OBJECTIVE: Cognitive deficits in older adults attributable to Alzheimer's disease (AD) pathology are featured early on by hippocampal impairment. Among tests used to evaluate memory, verbal memory tests with controlled encoding and cued recall are believed to be specific for hippocampal impairment. The objective of this study was to assess the relation between left and right hippocampal volumes and several frequently used memory tests. METHODS: Fifty six nondemented older adults (30 with amnestic mild cognitive impairment and 26 cognitively healthy older adults) underwent neuropsychological testing including: (1) The Enhanced Cued Recall test (ECR), a memory test with controlled encoding and recall; (2) the Auditory Verbal Learning Test (AVLT), a verbal memory test without controlled encoding and with delayed recall; and (3) The Rey-Osterrieth Complex Figure test (ROCF), a visuospatial memory test-recall condition. 1.5T brain MRI scans were used to measure estimated total intracranial volume (eTIV) along with hippocampal right and left volumes, which were measured with quantitative volumetry using FreeSurfer package (version 4.4.0). Spearman partial correlation controlled for age was used to correct for non-normal score distribution and effect of age. RESULTS: We found moderate correlations of hippocampal volumes with AVLT 1-5 scores, AVLT delayed recall, ECR free and total recall, and ROCF reproduction. Total recall in ECR using cued recall was not superior to any of the free recall tests. No correlation in any memory test was achieved with eTIV. CONCLUSION: Verbal memory tests, either with controlled encoding and cued delayed recall (ECR), or without it (AVLT), as well as nonverbal memory test with delayed recall (ROCF), equally reflect hippocampal atrophy in nondemented older adults.
Keywords: Neuropsychological Tests; senioři nad 80 let; Magnetic Resonance Imaging; retrospektivní studie; Humans; Image Processing, Computer-Assisted; neuropsychologické testy; Memory Disorders; lidé středního věku; Middle Aged; Aged, 80 and over; magnetická rezonanční tomografie; Atrophy; episodic memory; mužské pohlaví; atrofie; kognitivní poruchy; Hippocampus; Aging; počítačové zpracování obrazu; Amnestic mild cognitive impairment; poruchy paměti; hippocampus; ženské pohlaví; verbální učení; lidé; hipokampus; Cognition Disorders; Aged; MRI; senioři; Male; Retrospective Studies; Verbal Learning; stárnutí; Female